Bioengineered tumoral microtissues recapitulate desmoplastic reaction of pancreatic cancer. (February 2017) - Brancato, Virginia; Comunanza, Valentina; Imparato, Giorgia; Corà, Davide; Urciuolo, Francesco; Noghero, Alessio; Bussolino, Federico; Netti, Paolo A.
Graphical abstract: Abstract: Many of the existing three-dimensional (3D) cancer models in vitro fail to represent the entire complex tumor microenvironment composed of cells and extra cellular matrix (ECM) and do not allow a reliable study of the tumoral features and progression. In this paper we reported a strategy to produce 3D in vitro microtissues of pancreatic ductal adenocarcinoma (PDAC) for studying the desmoplastic reaction activated by the stroma–cancer crosstalk. Human PDAC microtissues were obtained by co-culturing pancreatic cancer cells (PT45) and normal or cancer-associated fibroblasts within biodegradable microcarriers in a spinner flask bioreactor. Morphological and histological analyses highlighted that the presence of fibroblasts resulted in the deposition of a stromal matrix rich in collagen leading to the formation of tumor microtissues composed of a heterotypic cell population embedded in their own ECM. We analyzed the modulation of expression of ECM genes and proteins and found that when fibroblasts were co-cultured with PT45, they acquired a myofibroblast phenotype and expressed the desmoplastic reaction markers. This PDAC microtissue, closely recapitulating key PDAC microenvironment characteristics, provides a valuable tool to elucidate the complex stroma–cancer interrelationship and could be used in a future perspective as a testing platform for anticancer drugs in tissue-on-chip technology. Statement of Significance: Tumor microenvironment is extremely complex and its organization is due to the interaction between different kind of cells and the extracellular matrix. Tissue engineering could give the answer to the increasing need of 3D culture model that better recapitulate the tumor features at cellular and extracellular level. We aimed in this work at developing a microtissue tumor model by mean of seeding together cancer cells and fibroblasts on gelatin microsphere in order to monitor the crosstalk between the two cell populations and the endogenous extracellular matrix deposition. Results are of particular interest because of the need of heterotypic cancer model that can replicate the complexity of the tumor microenvironment and could be used as drug screening platform.